Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1016/j.joca.2010.08.005
|View full text |Cite
|
Sign up to set email alerts
|

One in four people may develop symptomatic hip osteoarthritis in his or her lifetime

Abstract: Summary Objective To estimate the lifetime risk of symptomatic hip osteoarthritis (OA). Design We analyzed data from the Johnston County Osteoarthritis Project (a longitudinal population-based study of OA in North Carolina, United States [n=3,068]). The weighted baseline sample comprised 18% blacks and 54% women, and the mean age was 63 years (range=45-93). Symptomatic hip OA was defined as a Kellgren-Lawrence (K-L) radiographic score of ≥2 (anterior-posterior pelvis x-rays) and pain, aching or stiffness on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
211
0
10

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(236 citation statements)
references
References 37 publications
4
211
0
10
Order By: Relevance
“…1 The lifetime prevalence of symptomatic hip osteoarthritis is estimated at 25.3%, 2 while that of knee osteoarthritis is even higher at 44.7%. 3 The economic burden of osteoarthritis is substantial and consists of both direct costs (such as drugs,…”
Section: Introductionmentioning
confidence: 99%
“…1 The lifetime prevalence of symptomatic hip osteoarthritis is estimated at 25.3%, 2 while that of knee osteoarthritis is even higher at 44.7%. 3 The economic burden of osteoarthritis is substantial and consists of both direct costs (such as drugs,…”
Section: Introductionmentioning
confidence: 99%
“…Over 40 million Europeans are presently affected by OA [30]. Two studies have identified a 45% and 25% lifetime risk of developing knee and hip OA, respectively [31,32]. Furthermore, treatment is costly, currently estimated as representing 1:2.5% of gross national product [33].…”
Section: Asc Potential In Osteoarticular Disease: Osteoarthritis (Oa)mentioning
confidence: 99%
“…The disease known as hip osteoarthritis is a common highly painful disabling joint disease with no known cure affecting a large proportion of the adult population [1,2]. One potentially preventable factor that may mediate or moderate the onset and progression of hip osteoarthritis is obesity [3].…”
Section: Introductionmentioning
confidence: 99%